The influence of internet search engines and cellphones on the achievement of college of technology students in Cameroon - Fedelis Lekeaka Alemnge; Efuetngap Reginta (Eureka: Journal of Educational Research, 2025)
The rapid growth and sophistication of handheld phones, supported by accessible software, have made them indispensable for students, enabling instant access, storage, retrieval, and refinement of information anytime and anywhere. This study seeks to obtain insights into how the use of technology in teaching and learning influences students’ learning. Participants in the study revealed that the relationship between the Use of Search Engines (USE) in teaching and academic achievement of students in the College of Technology of the University of Buea was statistically significant. The correlation coefficient for the same relationship indicated a weak positive relationship, while qualitative data reveled that teachers held divergent, but positive views on how search engines were used in teaching. The qualitative findings on teachers’ views of how search engines influence students’ academic achievement also presented a variety of ways through which students consolidate their learning. Regarding the use of cellphones, students on the average reported favourable attitudes, implying that the relationship was statistically significant, while the correlation showed a moderate negative relationship. Teachers provided a variety of positive ways in which cellphones are used in teaching, and in relation to its influence on learning indicated that it increased their pace while fostering program coverage. They, however, indicted that it also caused distractions. Based on Rogers’ diffusion of innovation theory, educators should adapt technology use to adopter categories to enhance learning and reduce distractions.